Kulturbegreppet, kritiken och praktiken - Öhlander, Magnus (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1994)
Inspired by postmodernism, criticism has been directed against the tendency in the field of cultural studies to apprehend culture as an homogeneous entirety. This criticism is usually rubricized as "the reflexivity and representation debates". The assumption that culture is a priori common for a given group of people is the result fo the definitions which the concept has been given, but also of the way in which the researcher collects his material. The purpose of the present article is to examine and discuss the criticism of the concept of culture and its relevance for ethnological methodology. The article touches upon the problem of the ontology of the concept of culture and its connection with the ambition of interpreting and seeking implications in people’s life-worlds. Re-defining culture is not an effective enough way of unburdening the concept of these presumtions of homogeneity. Instead, this article proposes employing the term cultural phenomena. The degree to which homogeneity/complexity is to be found in a given culture is an empirical question. Finally, the article presents some thoughts on how the field between ethnography’s descriptive and more interpretive components can be opened up to scrutiny.